2016
DOI: 10.1111/jwas.12356
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effects of Dietary Prebiotic Mixture of Mannan Oligosaccharide and Poly‐β‐Hydroxybutyrate on the Growth Performance, Immunity, and Survival of Rainbow Trout, Oncorhynchus mykiss (Walbaum 1792), Fingerlings

Abstract: This study investigated the effects of dietary poly‐β‐hydroxybutyrate (PHB) and mannan oligosaccharide (MOS) on the growth performance, digestive enzyme activities, and disease resistance of rainbow trout fingerlings. A total of 420 fingerlings, distributed equally into four different groups, each with three replicates, were fed a basal diet (control), 2% PHB (PHB), 0.2% MOS (MOS), or a diet supplemented with a mixture of 2% PHB and 0.2% MOS (PHB+MOS) for 60 d. Results showed that dietary PHB and/or MOS did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…MOS are found in the outer layer of yeast, Saccharomyces cerevisiae , in the cell wall. As the most bioactive compounds, they contain both mannan proteins and complex carbohydrates, including β-glucans [4], and are widely used as a dietary supplement to boost the immune system and eliminate pathogens from the intestinal tract [5,6]. For instance, MOS bind to the mannose-specific lectin of Gram-negative pathogens that express Type-1 fimbriae (e.g., Escherichia coli ), resulting in their excretion from the intestine [7].…”
Section: Introductionmentioning
confidence: 99%
“…MOS are found in the outer layer of yeast, Saccharomyces cerevisiae , in the cell wall. As the most bioactive compounds, they contain both mannan proteins and complex carbohydrates, including β-glucans [4], and are widely used as a dietary supplement to boost the immune system and eliminate pathogens from the intestinal tract [5,6]. For instance, MOS bind to the mannose-specific lectin of Gram-negative pathogens that express Type-1 fimbriae (e.g., Escherichia coli ), resulting in their excretion from the intestine [7].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, PHB is found to be ineffective for survival rates of rainbow trout fry in this experiment. Najdegerami et al (2017) reported a confirmatory effect of the PHB on rainbow trout fingerlings in their research as well. Another similar result was also expressed in an experiment with European sea bass post‐larvae, in which Franke, Clemmesen, et al (2017) fed the fish with PHB‐enriched Artemia nauplii and reported that the PHB did not affect the survival rates of the animals.…”
Section: Discussionmentioning
confidence: 70%
“…Considering the data obtained, PHB has been found not to affect the growth and survival rates of rainbow trout fry in this trial ( p > .05). In a similar study, Najdegerami et al (2017) investigated the effects of dietary PHB (2%), mannan‐oligosaccharide (MOS) (0.2%), and their mixture (2% PHB + 0.2% MOS) on rainbow trout fingerlings; and found neither positive nor negative changes in the growth and survival parameters of fish as well. Literature reports that the dietary PHB is known not to affect the growth performance of blue mussel larvae (Van Hung et al, 2015), while it adversely affects the growth performance of Siberian sturgeon larvae (Najdegerami et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations